SISTEM MUá¸ŒÄ€RABAH DAN APLIKASINYA PADA BANK SYARIAH MANDIRI CABANG PALU - Ruslan, Murniati (State Institute of Islamic Studies (IAIN) Palu, 2013)
Abstract: Bank Syariah Mandiri is a state bank who first introduced a system of sharia. In a way, this bank was applying one system of cooperation with customers called muá¸Ärabah. The systems of muá¸Ärabah are also applicated in the Bank Syariah Mandiri Branch Palu, which was established in 2003. This study discusses the theory and application of muá¸Ärabah system in Bank Syariah Mandiri Branch Palu. The results showed that the application of muá¸Ärabah system in Bank Syariah Mandiri Branch Palu has not been fully realized purely in accordance with the theoretical foundation of muá¸Ärabah system suggested by experts, despite the commitment of Bank Syariah Mandiri Branch Palu to customers has increased significantly.Kata Kunci: aplikasi, sistem muá¸Ärabah, Bank Syarih Mandiri.